Elimination of oral focal infection: a new solution in chronic fatigue syndrome management? - Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2005)
Chronic fatigue syndrome (CFS) is an illness whose primary symptoms are debilitating fatigue and cognitive dysfunction. Substantial symptom overlaping with fibromyalgia, depression, allergic diseases, and many other illnesses, and the absence of a universally applicable diagnostic test, makes the diagnosis of CFS complex and challenging. The pathophysiology of CFS is also complex, and not clearly understood. Formerly, CFS was believed to be a variant form of depression, but due to an increasing body of evidence, CFS is now considered primarily as a biochemical derangement of the functioning of the neuroimmune and neuroendocrine systems. Recently, most treatments still primarily emphasize analgesics, anti inflammatory and psychiatric treatment which correlates to psychosomatic disorders. One of the symptoms that is poorly understood is allergy, but according to the neurogenic switching hypothesis the correlation can be explained nowadays. The role of oral focal infection as one of the possible etiology has still rarely been discussed. The goal of this article is to explain the possible pathophysiology of CFS which could be elicited by oral focal infection, especially endotoxin (lipopolysaccharide) from gram negative bacteria. This case report discusses the history of illness, previous treatments, diagnosis, case management and treatment result. Periodontal treatment of a patient with symptom mimicking CFSs undergoing periodontal treatment has a remarkable result. The conclusion is that the elimination of oral focal infection could be a new solution in CFS management.